1322-P: Combination of LiverSTAT (LST) and Fibroscan (LSM) Outperforms FIB-4 and LSM for MASLD Advanced Fibrosis (AF) F3F4 - ALKHOURI, NAIM; NADEEM, RIDA; LEFF, PHILLIP; MANTRY, PARVEZ; QUIAMBAO, RONALD; DUPUY, JULIE; MUNTEANU, MONA; DE LEDINGHEN, VICTOR (Diabetes (New York, N.Y.), 2024)
Background: LiverSTAT (LST) is a new blood test for MASLD stratification. Aims: To retrospectively compare the efficacy of two combinations in one-step approach with two combinations: LST&LSM versus FIB-4&LSM, for the identification of advanced fibrosis (F3F4) in a multicenter multiethnic meta-dataset of MASLD patients. Methods: Retrospective data from 5 hepatology centers from MASLD patients that underwent liver biopsy (LB) along with LSM, FIB-4 and LST. Efficiency has been assessed using concordance rates, number needed to screen (NNS) on subject with LB F3F4. Results: Data from 786 patients (22%US, 39%Asia, 39%EU) was analyzed [age 57.1years, female 54.5%, BMI 31.4, ALT 52U/L]. LB prevalence of F3F4 was 32.8%.In the overall cohort, LB confirmed F3F4 among concordant LST&LSM and FIB-4&LSM, respectively, in 107/142(75%) vs 54/64(84.4%) with a screening efficiency (NNS) of 1.8 vs 2.2; the combination LST&LSM correctly identified twice more F3F4 patients than FIB-4&LSM.In the subgroup with LB≥20mm, LB confirmed F3F4 among concordant LST&LSM and FIB-4&LSM in 43/50(86%) vs 30/33(90%), NNS 1.6 and 1.8, respectively; the combination LST&LSM correctly identified 43% more F3F4 patients than FIB-4&LSM.DFP rate was higher with FIB4-&LSM than with LST&LSM (11.3% vs. 7%). Conclusion: The combination LST&LSM outperforms FIB-4&LSM for the identification of MASH advanced fibrosis F3F4.